Between Pinela and Paris: emigration and return - Portela, José (2002)
The comparative analysis that this article puts forward shows how people become emigrants through necessity, by resonance and by being dragged along; the vigour of social networks; the key role of women; the interdependence between those who stay behind and those who leave; the way in which the new mobility is eroding the concept of emigration; resulting assets and achievements, symbols of breaking-off, here and there; the return, deep incision, tense sum of losses and prior acts.